Answer:
8.6 to the nearest tenth.
Step-by-step explanation:
Using the distance formula d = √ [(y2 - y1)^2 + (x2 - x1)^2] where (x1, y1) and (x2, y2) are the two endpoints.
= √ (4 - -3)^2 + (-3-2)^2
= √(49 + 25)
= 8.60
First, we find the slope
(4,0)(0,-3)
slope = (-3 - 0) / (0 - 4) = -3/-4 = 3/4
there can be 3 possible answers for this..
y - y1 = m(x - x1)
slope(m) = 3/4
using points (4,0)...x1 = 4 and y1 = 0
now we sub
y - 0 = 3/4(x - 4) <== this is one answer
y - y1 = m(x - x1)
slope(m) = 3/4
using points (0,-3)...x1 = 0 and y1 = -3
now we sub
y - (-3) = 3/4(x - 0) =
y + 3 = 3/4(x - 0) <== here is another answer
y - y1 = m(x - x1)
slope(m) = 3/4
using points (-4,-6)...x1 = -4 and y1 = -6
now we sub
y - (-6) = 3/4(x - (-4) =
y + 6 = 3/4(x + 4) <=== and here is another answer
Answer:
Step-by-step explanation: she only has 3 because of herself